Rancang Bangun Bahan Ajar Digital Berbasis Etnofisika pada Materi Dinamika Rotasi Berdasarkan Analisis Konstruksi Bangunan Kampung Pulo - LATIF FIRDAUS, MUHAMAD RAMDAN; Warliani, Resti; Irvani, Asep Irvan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to develop physics teaching materials that are feasible based on expert validity assessments. The developed digital teaching materials are considered suitable as they successfully integrate local wisdom with physics principles, particularly regarding aspects related to building structures and materials. Kampung Pulo, with its unique traditional architecture rich in cultural values and philosophy, serves as the main focus of this study to understand the physics phenomena inherent in its constructions. This research employs a development approach using a reduced 3D model of the FOUR-D (4D) development model. A mixed-methods approach was applied, including literature review, preliminary research, direct observation in Kampung Pulo, interviews with local figures and experts in traditional buildings, and analysis of the physical structure of existing buildings. The subjects for validation consisted of 4 material experts, 4 language experts, and 4 media experts. The results indicate that: (1) material validity was categorized as very good with a score of 93.22%, (2) language validity was categorized as very good with a score of 90.62%, and (3) media validity was categorized as very good with a score of 82.29%. Based on these results, it can be concluded that the developed physics teaching materials, based on ethnophysics and integrated with local wisdom, are feasible for use, supported by data showing very good validity across material, language, and media aspects.